An Unusually Big Cervical Fibroid Polyp : A Case Report - Khanam, Shireen Akhter; Rashid, Fahmida; Chowdhury, Shahanara (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2017)
Fibroid Uterus is the most common benign solid tumor in female. Most of fibroids situated in the body of the uterus, cervical myoma account 3% -8% of uterine myoma. Cervical myoma are uncommon in different presentation, resembling inversion of uterus, malignancy & various sizes are reported in literature. A case of big cervical fibroid polyp has been reported here. Patient presented something coming down per vagina with foul smelling discharge. On examinations there was a hugely enlarged, infected mass about 15cm x 12cm which was arising from posterior lip of the cervix & outside the introitus. As the patient was 45 years & had menorrhagia, Non Descend Vaginal Hysterectomy (NDVH) was done without resecting the polyp priorly. Patient was discharged in good condition. Histopathology confirmed the diagnosis and reported leiomyoma with areas of degeneration which was mainly composed of involuntary smooth muscle cells & fibrous connective tissue from cervix which probably expelled out as a polyp attached to posterior lip of cervix. Chatt Maa Shi Hosp Med Coll J; Vol.15 (2); Jul 2016; Page 65-67